TOURISTS’ AWARENESS AND UNDERSTANDING OF GAME DRIVE PROTOCOLS POST COVID-19 IN SOUTH AFRICA - Rabelani NEMAKANGA; Vyasha HARILAL; Tembi M. TICHAAWA (Geo Journal of Tourism and Geosites)
Embarking on a safari is a highly sought-after experience, attracting both local and global tourists in substantial numbers. Despite its widespread appeal, this type of experience entails inherent risks to both tourists and wildlife. This st udy aims to investigate the awareness and understanding of game drive protocols by tourists in South Afric a. Using the Greater Kruger National Park, adopting an explanatory qualitative research approach, thirty-one semi-structured in-depth interviews were conducted from different safari tourism stakeholders, including safari lodge managers, park authorities and tour guides. The study revealed varied levels of awareness and understanding of game drive protocols by tourists during safari experiences in both private and national park contexts. The causes are attributed to a lack of awareness of protocols and guide lines, selfguided safaris, lack of law enforcement presence (field guides and rangers), insufficient induction, and language and cultura l barriers, among others. As a consequence, tourists non-compliance behaviour was found to not only have negative consequences on wildlife and the ecosystem generally, but also endanger themselves and other tourists, and threaten the safari tourism sustainability and livelihoods. The study has implications for the enforcement of tourist compliance to game drive protocols, to ensure tourists safety and animal welfare, as well as to increase the overall experience whilst on guided or selfguided safari in game reserves.